(untitled) (Research, Society and Development, 2021)
We present to outline a theoretical framework on teacher professional development from systematization and discussion of main theoretical categories underpinning this process, which are prevalent in the international research on teacher education. With the aim of highlighting and discussing the dimensions underlying the professional development of teachers, we carried out a systematic literature review that allowed us to form a framework of the main categories addressed by the related theorists related to the teacher professional development, who are most referenced in the Google Scholar and with an h-Scopus index higher than 20. The qualitative analyses reveal five categories underpinning teacher professional development: professional knowledge, which characterizes the basic theoretical subsidies to teaching; professional learning, conceived as a process of improving teacher knowledge on teaching practice; professional culture, values, habits, and practices legitimized by groups of teachers; the ethical dimension of teaching, which designates individual and collective commitment to overcoming inequalities in educational and social opportunities; and changes in the practice, understood as processes of criticism and modification of classroom practices, beliefs, and dispositions of teachers.